Park Facilities Evaluation Based on Neighborhood Quality and Differences in Gender Perception in Cimahi Apartment - Permatasari, Gladya Putri; Sugiama, Aceng Gima (Universitas Islam Sultan Agung, 2026)
The physical facilities of apartment parks are crucial, yet studies on this subject are scarce. This study aims to evaluate apartment park facilities based on neighborhood quality (accessibility, attractiveness, functionality, safety) and investigate differences in gender perception. Using a quantitative approach, the data is analyzed using descriptive statistics and the Mann-Whitney U test. Using data from 133 respondents, the study results found, descriptively, accessibility is in good condition but the pedestrian path is slightly damaged and has not been equipped with information boards; attractiveness is still lacking to improve aesthetics and ensure the cleanliness of the park; functionality for sports facilities is not yet available, and seating and children's play areas are uncomfortable; and safety has been met, but lighting at night is inadequate. The results also showed, generally, no significant difference between the assessments of the park's physical facilities by the two genders. However, specifically, there were significant differences in perceptions of proximity, vegetation availability, and trash receptacle availability. This study is expected to serve as a reference in creating apartment parks by integrating quality neighborhood parks and designing park facilities that function inclusively for both males and females. Keywords: physical asset facility, low-cost apartment, neighborhood park quality.